2023
DOI: 10.1162/jocn_a_01969
|View full text |Cite
|
Sign up to set email alerts
|

Low Vision Impairs Implicit Sensorimotor Adaptation in Response to Small Errors, But Not Large Errors

Abstract: Successful goal-directed actions require constant fine-tuning of the motor system. This fine-tuning is thought to rely on an implicit adaptation process that is driven by sensory prediction errors (i.e., where you see your hand after reaching vs. where you expected it to be). Individuals with low vision experience challenges with visuomotor control, but whether low vision disrupts motor adaptation is unknown. To explore this question, we assessed individuals with low vision and matched controls with normal vis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
1
1
0
Order By: Relevance
“…6c, h ). Recently, similar results were reported when the uncertainty of visual feedback was manipulated 6 or when the adaptation was tested for low vision participants 41 . The authors tried to explain the result by assuming that the distribution of dots is truncated below a certain threshold due to the inherent saturation property of the learning response (i.e., the learning response remains almost unchanged to the error beyond the threshold level).…”
Section: Discussionsupporting
confidence: 75%
“…6c, h ). Recently, similar results were reported when the uncertainty of visual feedback was manipulated 6 or when the adaptation was tested for low vision participants 41 . The authors tried to explain the result by assuming that the distribution of dots is truncated below a certain threshold due to the inherent saturation property of the learning response (i.e., the learning response remains almost unchanged to the error beyond the threshold level).…”
Section: Discussionsupporting
confidence: 75%
“…A recent study reported that motor impairments were weak-moderately associated with reductions in visuomotor adaptation after stroke [ 26 ]. Together, the results point to the possibility that other factors, including visual or cognitive function [ 85 , 86 ] may play into distinct profiles of impairment in motor adaptation in the early weeks and months after stroke. Some evidence in older adults suggest that reductions in visuomotor adaptation may be related to cognitive decline [ 87 ].…”
Section: Discussionmentioning
confidence: 88%